Порівняльний аналіз методів вирощування кристалів - Бойчук, О. Г. (ХНУРЕ, 2021)
The report will consider some methods of growing artificial crystals, namely the Czochralski method and the Kyropoulos method. The main advantages and principles of these methods. Also, a comparative characteristic of these methods of growing artificial crystals will be carried out. Let's evaluate the quality of the crystal depending on the method.
Keywords: метод вирощування кристалів